Sustainable Management Coping with the Dilemmas of Resource-Oriented Management - Müller-Christ, Georg (Springer Berlin Heidelberg Imprint: Springer, 2011)
In this book, a resource-oriented perception of sustainable management is presented. Firms that decide to act more sustainable have to bear in mind that they do not only need resources for economic activities today, but that they will need these tomorrow as well. This leads to contradictory management rationalities firms must deal with. The author presents his findings as regards the development of environmental and social responsibility and introduces a theory of management ecology. He takes a close look at the contradictions businesses have to face when governing their activity towards sustainability. Moreover, he identifies different notions of the resource term in management studies and develops a ?sustainable resource management? which could help businesses redirect their economic activities from a solely profit-oriented to a resource-oriented way of operating.